The Analysis of Organizational Capacity Factors in Government Division of Regional Secretariat as A Determinant of Government Performance at Batang Regency - Listyaningsih Dewi Pamungkas; Kismartini Kismartini; Retno Sunu Astuti (Iapa Proceedings Conference, 2020)
As the leader of the implementation of governmental affairs which become the authority of regional government, based on the mandate of Law Number 23 Year 2014 on Regional Government, the Head of regional government is obliged to prepare Regional Government Administration Report (RGAR) which by the central government will be used as material for evaluation and guidance to implement the administration of regional government. Batang Regency is the only Regency which for the last respective three years (2016, 2017 and 2018) has been in the 5th rank (the lowest five) in Central Java. The results of this evaluation are used as material for the Ministry of Finance in determining the Regional Incentive Fund and for the Ministry of Home Affairs in approving additional income for state civil apparatus. However, Batang Regency has not yet optimized its reporting system and Evaluation of Regional Government Administration Performance. Due to this unoptimal evaluation results on the implementation of regional Government, organizational capacity and the evaluation of the Governmental Division at Batang Regency regional Secretariat as the division who conducted the report preparation activities became the focus of this research. Qualitative descriptive method was used to describe all the symptoms / conditions which exist during the research. Moreover, the analysis was carried out through data reduction, display data and conclusion drawing / verification. Based on the results of this research, it can be concluded that the Organizational Capacity of the Government division of the Regional Secretariat of Batang Regency which involves some resources (human resources, infrastructure, technology and financial resources) and management (leadership, program and process management as well as cooperation and relationships among organizations) needs to be improved, such as conducting job analysis, increasing the quantity and quality of human resources, making more detail activities planning and budgeting as well as defending them during budget discussions, making Terms of Reference and improving effective communication skills.